2019
DOI: 10.1016/j.palaeo.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of benthic communities following the Toarcian oceanic anoxic event in the Cleveland Basin, UK

Abstract: During the Toarcian oceanic anoxic event (OAE) considerable environmental changes occurred that were associated with global warming, perturbations to the Ccycle and ocean deoxygenation which resulted in a mass extinction of marine fauna. Recovery of the biota after the event was protracted and has to date undergone limited study. However, understanding the patterns and processes of recovery are critical to anticipating ecosystem responses to the environmental changes predicted for the near future. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 121 publications
1
7
0
Order By: Relevance
“…This result is in line the lithological evidence for anoxia/dysoxia (i.e. organic-rich black shales) within the Cleveland Basin 38 and provides confidence that our method is performing well.…”
Section: Extinction Dynamicssupporting
confidence: 83%
See 1 more Smart Citation
“…This result is in line the lithological evidence for anoxia/dysoxia (i.e. organic-rich black shales) within the Cleveland Basin 38 and provides confidence that our method is performing well.…”
Section: Extinction Dynamicssupporting
confidence: 83%
“…It has been hypothesised that D. ovum may have been able to survive epifaunally before oxygenation improved within the sediment and then subsequently acted as an ecosystem engineer that catalysed the re-oxygenation of the sediment via bioirrigation 38 . D. ovum is representative of the first infaunal guild to reappear, some 1 million years after the extinction event 38,39 , and is then followed by subsequent shallow and deep infaunal taxa by the end of the early recovery interval. Whilst the epifaunal community is still dominated by sessile or facultatively mobile taxa, oxygenation of bottom waters is further indicated by the return of motile predatory and grazing guilds (i.e.…”
Section: Ecosystem Recovery Following the Etementioning
confidence: 99%
“…The succession of species within the genera Gresslya, Pholadomya, Oxytoma and also Cardinia show perhaps the best candidates for Cope's Rule. Although insufficient material was measured during this study, Hodges (2000) also found an increase in size between Dacryomya heberti (Martin) and D. gaveyi Cox between the Sinemurian and Pliensbachian, a size trajectory that appears to have been sustained in to the Toarcian with D. ovum (J. de C. Sowerby) (Caswell and Dawn, 2019). This therefore suggests that Cope's Rule did play a role in the size increase in the Lower Jurassic, but the Brobdingnag Effect is more crucial to explain the large bivalves of the spinatum Chronozone.…”
Section: Cope's Rulementioning
confidence: 73%
“…Biotic consequences of the T-OAE were far-reaching reorganizations of marine and terrestrial flora and fauna, including severe extinctions and protracted recovery from the loss of biodiversity [20][21][22][23][24] . The magnitude and duration of the greenhouse warming that must have been associated with the large-scale release of methane and carbon dioxide into the atmosphere, however, has so far been hard to quantify reliably.…”
mentioning
confidence: 99%